On the symmetries of the 6j symbol - Newmarch, J.D. (AIP Publishing, 1983)
The 6j tensor for compact groups is shown to transform as a basis vector for the identity representation of the permutation group S4. This allows character theory to be used to determine the minimum number of independent components and a projection operator to determine the relations between components-the symmetry properties.